Analisis Budaya Patriarki Dalam Pemilihan Karir Mahasiswi Tingkat Akhir Pada Universitas Sahid Surakarta - Indah Puji Rahayu (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the influence of patriarchal culture on the career choices of final year female students at Sahid University Surakarta. Using qualitative methods, data was collected through in-depth interviews with seven main informants and two supporting informants. The results showed that patriarchal culture significantly influences the career choices of female college students, with men dominating important positions in academic and professional environments. Female college students face limited career opportunities in education and social fields, while leadership roles are dominated by men. While reproductive health services are generally adequate, the quality of off-campus facilities needs to be improved. Women also feel less safe in public spaces and their participation in public activities and economic decision-making remains limited. This research suggests universities provide mentoring programs and leadership training for female students, offer diverse internship opportunities, and promote gender equality through educational campaigns and supportive policies. This research is expected to provide new insights into the influence of patriarchal culture on women's career choices.